Early category and concept development : making sense of the blooming, buzzing confusion - Rakison, David H., 1969-; Oakes, Lisa M., 1963- (Oxford ; New York : Oxford University Press, 2003)
This text brings together contemporary findings and theories about the origins and early development of categorization and conceptual abilities. Despite advances in our understanding of this area, a number of hotly debated issues remain at the centre of the controversy over categorization.
Making an ontology : cross-linguistic evidence / Linda B. Smith, Eliana Colunga, and Hanako Yoshida -- Words, kinds, and causal powers : a theory theory perspective on early naming and categorization / Alison Gopnik and Thierry Nazzi -- Theory-based categorization in early childhood / Susan A. Gelman and Melissa A. Koenig -- Acquisition and use of implicit categories in early development / Denis Mareschal -- Commentary on Part II : abilities and assumptions underlying conceptual development / Ellen M. Markman and Vikram K. Jaswal -- Final commentary : conceptual development from origins to asymptotes / Robert L. Goldstone and Mark K. Johansen.
Includes bibliographical references and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Cognition in infants; Perception in infants; Cognition; Child development; Perception; Children; Infants; Cognition; Child Development; Concept Formation; Perception; Child; Infant; Cognition chez le nourrisson; Perception chez le nourrisson; Cognition; Enfants -- Développement.; Perception; Enfants; Nourrissons; cognition; children (people by age group); infants; FAMILY & RELATIONSHIPS -- Life Stages -- Infants & Toddlers; Perception; Infants; Cognition; Children; Child development; Cognition in infants; Perception in infants; Samfundsvidenskab -- Psykologi